2021
DOI: 10.1109/access.2021.3091427
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Cross-Architectural IoT Malware Threat Hunting

Abstract: In recent years, the increase in non-Windows malware threats had turned the focus of the cybersecurity community. Research works on hunting Windows PE-based malwares are maturing, whereas the developments on Linux malware threat hunting are relatively scarce. With the advent of the Internet of Things (IoT) era, smart devices that are getting integrated into human life have become a hackers' highway for their malicious activities. The IoT devices employ various Unix-based architectures that follow ELF (Executab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 64 publications
0
20
0
2
Order By: Relevance
“…The particular difficulty of conducting SA is manifested precisely for IoTS, which have different functional purposes. Thus, devices use various OS, distros and CPU architectures [ 16 ]. Each such choice, in particular, is selected based on the tasks of the devices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular difficulty of conducting SA is manifested precisely for IoTS, which have different functional purposes. Thus, devices use various OS, distros and CPU architectures [ 16 ]. Each such choice, in particular, is selected based on the tasks of the devices.…”
Section: Methodsmentioning
confidence: 99%
“…The work [ 16 ] emphasizes the relevance and underdevelopment of solutions for the search for malicious IoT software. Particular attention is paid to the executed Unux-like programs in the ELF format.…”
Section: Analysis Of Existing Review Workmentioning
confidence: 99%
“…Most of them do not discuss the role of AI [27]. Moreover, some relevant surveys discuss threat hunting in a specific area [28]. These shortcomings motivate our work in this paper.…”
Section: Existing Surveysmentioning
confidence: 99%
“…Threat hunting is important for all types of technologies. In [28] it was identified that there is a lack of research regarding non-Windows operating systems. There is constant development of hunting techniques for Windows malware, but there is a lack of work regarding Linux protection [28].…”
Section: Surveys On Threat Huntingmentioning
confidence: 99%
“…The practice of contaminating web applications with malevolent software is termed malware. In Recent Times, a massive number of malwares has been devised for attacking IoT systems [75,76] Control flow side-channel assessment [77], software integrity validation, malware detector [78], Security updates [79] (continued) Reverse Engineering All An attempt to analyze the firmware of IoT devices to reach sensitive data i.e., users' credentials [93] Self-destruction and Tamper proofing, IC/IP Obfuscation and encryption [94,95] (continued) Identity and access management, authentication, multi-factor authentication guidance, dynamic credentials [100] Brute-force attacks S4, S6 An active attack hinges on a trial-and-error strategy to obtain some data such as passwords, finance, identifiers. It employs automatic software to engender a massive amount of successive suppositions to decrypt the ciphertext [85,86] Locking out IP address, discovery tools, brute force site scanning tools [101] Data exposure attacks…”
Section: Allmentioning
confidence: 99%